Herpes Simplex Virus 1 UL2 Inhibits the TNF-α–Mediated NF-κB Activity by Interacting With p65/p50 - Cai, Mingsheng; Liao, Zongmin; Zou, Xingmei; Xu, Zuo; Wang, Yuanfang; Li, Tong; Li, Yiwen; Ou, Xiaowen; Deng, Yangxi; Guo, Yingjie; Peng, Tao; Li, Meili (Frontiers in Immunology, 2020)
Herpes simplex virus 1 (HSV-1) is a large double-stranded DNA virus that encodes at least 80 viral proteins, many of which are involved in the virus–host interaction and are beneficial to the viral survival and reproduction. However, the biological functions of some HSV-1–encoded proteins are not fully understood. Nuclear factor κB (NF-κB) activation is the major antiviral innate response, which can be triggered by various signals induced by cellular receptors from different pathways. Here, we demonstrated that HSV-1 UL2 protein could antagonize the tumor necrosis factor α (TNF-α)–mediated NF-κB activation. Co-immunoprecipitation assays showed that UL2 could interact with the NF-κB subunits p65 and p50, which also revealed the region of amino acids 9 to 17 of UL2 could suppress the NF-κB activation and interact with p65 and p50, and UL2 bound to the immunoglobulin-like plexin transcription factor functional domain of p65. However, UL2 did not affect the formation of p65/p50 dimerization and their nuclear localizations. Yet, UL2 was demonstrated to inhibit the NF-κB activity by attenuating TNF-α–induced p65 phosphorylation at Ser536 and therefore decreasing the expression of downstream inflammatory chemokine interleukin 8. Taken together, the attenuation of NF-κB activation by UL2 may contribute to the escape of host’s antiviral innate immunity for HSV-1 during its infection.